Treatment stage migration and treatment sequences in patients with hepatocellular carcinoma: drawbacks and opportunities - Wehling, Cyrill; Dill, Michael T.; Olkus, Alexander; Springfeld, Christoph; Chang, De-Hua; Naumann, Patrick; Longerich, Thomas; Kratochwil, Clemens; Mehrabi, Arianeb; Merle, Uta; Pfeiffenberger, Jan; Rupp, Christian; et al. (Journal of cancer research and clinical oncology, 2021)
Purpose  This retrospective analysis focuses on treatment stage migration in patients with hepatocellular carcinoma (HCC) to identify successful treatment sequences in a large cohort of real-world patients. - Methods  1369 HCC patients referred from January 1993 to January 2020 to the tertiary center of the Heidelberg University Hospital, Germany were analyzed for initial and subsequent treatment patterns, and overall survival. - Results  The most common initial treatment was transarterial chemoembolization (TACE, n = 455, 39.3%) followed by hepatic resection (n = 303, 26.1%) and systemic therapy (n = 200, 17.3%), whereas the most common 2nd treatment modality was liver transplantation (n = 215, 33.2%) followed by systemic therapy (n = 177, 27.3%) and TACE (n = 85, 13.1%). Kaplan-Meier analysis revealed by far the best prognosis for liver transplantation recipients (median overall survival not reached), followed by patients with hepatic resection (11.1 years). Patients receiving systemic therapy as their first treatment had the shortest median overall survival (1.7 years; P < 0.0001). When three or more treatment sequences preceded liver transplantation, patients had a significant shorter median overall survival (1st seq.: not reached; 2nd seq.: 12.4 years; 3rd seq.: 11.1 years; beyond 3 sequences: 5.5 years; P = 0.01). - Conclusion  TACE was the most common initial intervention, whereas liver transplantation was the most frequent 2nd treatment. While liver transplantation and hepatic resection were associated with the best median overall survival, the timing of liver transplantation within the treatment sequence strongly affected median survival.